Time capsule signature: Efficient and provably secure constructions - HU, Bessie C. (Institutional Knowledge at Singapore Management University, 2007)
Time Capsule Signature, first formalized by Dodis and Yum in Financial Cryptography 2005, is a digital signature scheme which allows a signature to bear a (future) time t so that the signature will only be valid at time t or later, when a trusted third party called time server releases time-dependent information for checking the validity of a time capsule signature. Also, the actual signer of a time capsule signature has the privilege to make the signature valid before time t.In this paper, we provide a new security model of time capsule signature such that time server is not required to be fully trusted. Moreover, we provide two efficient constructions in random oracle model and standard model. Our improved security model and proven secure constructions have the potential to build some new E-Commerce applications.